Peran Brand Image Dan Persepsi Harga Terhadap Keputusan Pembelian Produk Body Lotion Di Kota Ambon - Rika Mahra Tjira; Victor R Pattipeilohy; Stevanus. J. Gomies; Vascolino Pattipeilohy (P3M Politeknik Negeri Ambon, 2024)
This study aims to analyze the influence of brand image and price perception on the purchase decision of Scarlett Whitening body lotion products in Ambon City. Scarlett Whitening body lotion has received various complaints that diminish consumer comfort and satisfaction, such as the product not providing as much benefit as competitors in a similar price range. A sample of 100 respondents was selected using non-probability sampling with a purposive sampling approach. Data was collected through a survey by distributing questionnaires to consumers. The analytical method used was multiple linear regression analysis with the assistance of SPSS software version 22.0. The results of the study show that hypothesis one produced a t-count value of 2.064 and a table distribution value at a 5% significance level of 1.661, yielding a t-count > t-table result, or 2.064 > 1.661, with a significance level of less than 0.05 (0.042 < 0.05). For hypothesis two, a t-count of 7.857 was obtained with a table value of 1.661, resulting in t-count > t-table, or 7.857 > 1.661, with a significance level also less than 0.05 (0.000 < 0.05). Based on the study's findings, it can be concluded that both brand image and price perception variables have a positive and significant influence on purchase decision. Brand image has a significant positive effect on purchase decision for Scarlett Whitening body lotion products in Ambon City. Price perception has a stronger influence on purchase decision for Scarlett Whitening body lotion products in Ambon City compared to brand image.